# 6(3t-4)+10=5(t-2)-(3t-4)

## Simple and best practice solution for 6(3t-4)+10=5(t-2)-(3t-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6(3t-4)+10=5(t-2)-(3t-4) equation:

Simplifying
6(3t + -4) + 10 = 5(t + -2) + -1(3t + -4)
Reorder the terms:
6(-4 + 3t) + 10 = 5(t + -2) + -1(3t + -4)
(-4 * 6 + 3t * 6) + 10 = 5(t + -2) + -1(3t + -4)
(-24 + 18t) + 10 = 5(t + -2) + -1(3t + -4)
Reorder the terms:
-24 + 10 + 18t = 5(t + -2) + -1(3t + -4)
Combine like terms: -24 + 10 = -14
-14 + 18t = 5(t + -2) + -1(3t + -4)
Reorder the terms:
-14 + 18t = 5(-2 + t) + -1(3t + -4)
-14 + 18t = (-2 * 5 + t * 5) + -1(3t + -4)
-14 + 18t = (-10 + 5t) + -1(3t + -4)
Reorder the terms:
-14 + 18t = -10 + 5t + -1(-4 + 3t)
-14 + 18t = -10 + 5t + (-4 * -1 + 3t * -1)
-14 + 18t = -10 + 5t + (4 + -3t)
Reorder the terms:
-14 + 18t = -10 + 4 + 5t + -3t
Combine like terms: -10 + 4 = -6
-14 + 18t = -6 + 5t + -3t
Combine like terms: 5t + -3t = 2t
-14 + 18t = -6 + 2t
Solving
-14 + 18t = -6 + 2t
Solving for variable 't'.
Move all terms containing t to the left, all other terms to the right.
Add '-2t' to each side of the equation.
-14 + 18t + -2t = -6 + 2t + -2t
Combine like terms: 18t + -2t = 16t
-14 + 16t = -6 + 2t + -2t
Combine like terms: 2t + -2t = 0
-14 + 16t = -6 + 0
-14 + 16t = -6
Add '14' to each side of the equation.
-14 + 14 + 16t = -6 + 14
Combine like terms: -14 + 14 = 0
0 + 16t = -6 + 14
16t = -6 + 14
Combine like terms: -6 + 14 = 8
16t = 8
Divide each side by '16'.
t = 0.5
Simplifying
t = 0.5`